Analysis of Collaboration Ability in the RADEC Learning Model for Elementary School Students - As'ary, Mohamad Yasin; Sujana, Atep; Sopandi, Wahyu (Mimbar Sekolah Dasar, 2024)
This study investigates the effectiveness of the Read, Answer, Discuss, Explain, and Create (RADEC) learning model in fostering collaboration skills among elementary school students during electricity science lessons. Collaboration is defined as a group effort aimed at achieving a shared goal. A descriptive qualitative research method was employed, involving 24 sixth-grade students from an elementary school in Bandung City, Indonesia. Data were collected using questionnaires and observation sheets. The results indicated that students’ collaboration skills averaged 84% based on observations and 82% based on questionnaire responses, both categorized as good. The assessment was based on indicators of collaboration, including positive interdependence, face-to-face interaction, individual accountability, group communication, and group processes. These findings suggest that the RADEC learning model can serve as a useful approach for teachers to develop students' collaborative abilities. Furthermore, this model promotes student engagement and teamwork, enhancing the overall quality of learning experiences in elementary education.